2009
DOI: 10.1007/bf03395672
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Peer Monitoring Training on the Emergence of the Capability to Learn from Observing Instruction Received by Peers

Abstract: We tested the effects of teaching peer monitoring on the emergence of an observational learning (OL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Observational learning has been defined as the learning of new responses that occurs as a result of observing the responding of a model and the consequences that this responding produces (Catania, 1998). The potential benefits of observational learning cannot be understated; if one can learn by observing the responses of others, it may reduce instruction time, maximize learning opportunities in mainstream learning environments, and permit the acquisition of novel information without explicit instruction (Delgado & Greer, 2009;. As several researchers have noted, however, observational learning may require some specific prerequisite skills, such as attention to a model, generalized imitation, and the demonstration of complex discriminations (Deguchi, 1984;Greer et al, 2006;Masia & Chase, 1997).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Observational learning has been defined as the learning of new responses that occurs as a result of observing the responding of a model and the consequences that this responding produces (Catania, 1998). The potential benefits of observational learning cannot be understated; if one can learn by observing the responses of others, it may reduce instruction time, maximize learning opportunities in mainstream learning environments, and permit the acquisition of novel information without explicit instruction (Delgado & Greer, 2009;. As several researchers have noted, however, observational learning may require some specific prerequisite skills, such as attention to a model, generalized imitation, and the demonstration of complex discriminations (Deguchi, 1984;Greer et al, 2006;Masia & Chase, 1997).…”
mentioning
confidence: 99%
“…Two recent studies have attempted to isolate component responses related to observational learning and to determine the effects of learning these responses on the emergence of new responses during observational learning sessions (Delgado & Greer, 2009;Taylor, DeQuinzio, & Stine, 2012). evaluated a procedure for teaching children with autism to learn new sight words by watching a peer engage in an instructional interaction with a teacher.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…VL involves observing and imitating a model but also, importantly, requires simple and complex discriminations among consequences received by the model [61,230,233,239,252,264,265,[272][273][274]. Twenty-one studies reviewed in [230] concluded that some children with ASD appear to be deficient in imitative skills.…”
Section: Discussionmentioning
confidence: 99%